Isotonic solution for management of high output fistula and stoma - Marvin Marino; Yosua Yan Kristian; Evania Astella Setiawan; Gabriella Nurahmani Putri; Pauline Octaviani; Diana Sunardi (World Nutrition Journal, 2022)
Enterocutaneous fistulae (ECF) is a common complication in open abdominal surgeries which is commonly fixed by creating a stoma. High-output ECF defined as production of fistulae more than 500 mL per day. It is one of the complications that can occur in the presence of a stoma, and it is associated with significant morbidity and mortality. Therefore, adequate management of high output ECF and stoma is important. Administration of isotonic solution is one of techniques proven to be beneficial in reducing stoma output and allowing persistent luminal stimulation. We reported a case of high-ileostomy and ECF output in which isotonic solution conveyed improvement in clinical outcome.